2019
DOI: 10.1038/s41598-019-43542-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessing matrix quality by Raman spectroscopy helps predict fracture toughness of human cortical bone

Abstract: Developing clinical tools that assess bone matrix quality could improve the assessment of a person’s fracture risk. To determine whether Raman spectroscopy (RS) has such potential, we acquired Raman spectra from human cortical bone using microscope- and fiber optic probe-based Raman systems and tested whether correlations between RS and fracture toughness properties were statistically significant. Calculated directly from intensities at wavenumbers identified by second derivative analysis, Amide I sub-peak rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 60 publications
3
45
3
Order By: Relevance
“…While increased collagen disorder is associated with decreased bone fatigue failure cycle number in human bone, 47 these correlations explain only a subset of the mineralized tissue biomechanics. Bone possesses numerous toughening mechanisms, and correlations between fracture toughness and other bone properties are typically weak‐to‐moderate ( R 2 ≈ 25%) 48 . The numerous, nuanced mechanisms that may regulate post‐radiotherapy bone fragility are not well characterized in models of therapeutic radiation dosing, although somewhat better understood from kGy irradiation experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While increased collagen disorder is associated with decreased bone fatigue failure cycle number in human bone, 47 these correlations explain only a subset of the mineralized tissue biomechanics. Bone possesses numerous toughening mechanisms, and correlations between fracture toughness and other bone properties are typically weak‐to‐moderate ( R 2 ≈ 25%) 48 . The numerous, nuanced mechanisms that may regulate post‐radiotherapy bone fragility are not well characterized in models of therapeutic radiation dosing, although somewhat better understood from kGy irradiation experiments.…”
Section: Discussionmentioning
confidence: 99%
“…18,20 While an increase in trivalent:divalent crosslinking could increase bone strength, 44 [12][13][14]18,20 The effects of radiation on bone are generally much larger than the toughness and other bone properties are typically weak-to-moderate (R 2 ≈ 25%). 48 The numerous, nuanced mechanisms that may regulate post-radiotherapy bone fragility are not well characterized in models of therapeutic radiation dosing, although somewhat better understood from kGy irradiation experiments. It has long been recognized that the viscoelastic properties of bone can be related to bone strength.…”
Section: Collagen Fragmentationmentioning
confidence: 99%
“…of the variance in human cortical bone's fracture resistance over a range of ages (Unal et al, 2019). PCs derived from full Raman spectra of human cortical bone specimens have been shown to correlate strongly with fracture mechanics properties such as crack growth toughness and initiation (Makowski et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that Raman spectroscopy can predict femoral fracture toughness for a rheumatoid arthritis model (Inzana et al, 2013). Others have demonstrated that Raman-derived features can be incorporated in multivariable linear models to predict up to 50% of the variance in human cortical bone’s fracture resistance over a range of ages (Unal et al, 2019). PCs derived from full Raman spectra of human cortical bone specimens have been shown to correlate strongly with fracture mechanics properties such as crack growth toughness and initiation (Makowski et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of Raman bands results in outcomes mostly equivalent to those obtained by FTIR spectroscopy, such as quantification of tissue mineralization, mineral crystallinity, amount of carbonate substitutions in the mineral, and collagen maturity [ 2 , 16 ] ( Table 6 ). Raman spectroscopy and imaging have been widely applied to investigate bone mineral and matrix composition, as it can be illustrated by numerous publications on the subject [ 35 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 ], including several comprehensive reviews published in the last decade [ 2 , 16 , 17 , 18 , 61 , 153 ]. In particular, we can highlight two reviews by Morris and Mandair [ 18 ] and Mandair and Morris [ 17 ] which focus specifically on the application of Raman spectroscopy to assess bone quality and strength.…”
Section: Application Of Vibrational Spectroscopy For Connective Timentioning
confidence: 99%